Strategic resources, environmental management accounting (EMA) and business performance of Sabah construction industry / Sitti Syamsiar Muharram (Institute of Graduate Studies, UiTM, 2017)
The construction industry and its activities are among the major sources of economic growth and development in Malaysia and across the world. Like other countries, the construction industry in Malaysia also encounters a lot of challenges such as the delay to complete the project in time, the expenditure exceeding the budget, the building defects and over dependent on foreign workers, construction waste, and poor productivity. These consequently contribute to poor performance, especially in terms of cost and time overrun. The purpose of this study was to examine the relationship between strategic resources (tangible resources, intangible resources, and dynamic capabilities) and business performance. Additionally, the study aims to examine the moderating effect of environmental management accounting (EMA) in the relationship between strategic resources (tangible resources, intangible resources, and dynamic capabilities) and business performance. This study uses self-administered questionnaires where respondents were selected using stratified random sampling from construction companies in Sabah.